A preliminary intervention to improve brand awareness for smart parking apps (Open International Journal of Informatics, 2021)
The high number of vehicles on the road and demand for secure and efficient parking space brought many introductions to online parking system globally. JomParking, is a smart parking service system, designed to deal with parking problems in Malaysia. The application is developed by a company called JomParkir, advocates green life, hoping that people will no longer use cash or receipts and move towards digitalization. The ‘digitalization’ of the enterprise sector is in line with the current lifestyle and the growing needs for digital products and services. However, new digital services offered are often faced with challenges. This paper presents a study to improve the brand awareness of smart parking application, and uses JomParkir as an example to illustrate the challenges that the technology company faced in its digital marketing process. Data of the study was collected through interviews and online observation. Based on the findings, recommendations to improve JomParkir’s digital marketing initiatives are proposed.
Keywords: digital marketing; brand awareness; smart parking app; artificial intelligence